Analisis Kepatuhan Wajib Pajak Pada UMKM Di Kota Medan - Junawan Junawan (Jurnal Riset AKuntansi dan Bisnis, 2022)
This study aims to examine and analyze the effect of taxpayer behavior and economic factors, as well as tax justice on taxpayer compliance. The population of this study includes SME registered at the North Sumatra I Regional Tax Office in Medan, amounting to 200,000 SME, and using the accidental sampling technique. Data analysis used multiple linear regression. The results showed that simultaneously the behavior of taxpayers, economic factors, and tax justice had a significant effect on taxpayer compliance. Partially, the variables of taxpayer behavior and economic factors have a significant positive effect on taxpayer compliance, but tax justice has no effect on taxpayer compliance.